TEDDEEC: Threshold Enhanced Developed Distributed Energy-Efficient Clustering Protocol for Heterogeneous Wireless Sensor Networks - Sharma, Aditi; Singh, Harjit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In wireless sensor networks, hundreds or thousands of sensor networks are deployed in a field to sense data (like temperature, light, pressure, sound etc.) and then they transmit it to sink nodes or base station via a radio transmitter. At one side where these networks have numerous applications, they suffer from a major disadvantage on the other side. These sensor nodes are power constrained and hence they have limited lifetime. Once deployed, these nodes cannot be recharged, therefore researchers are developing protocols to enhance network lifetime. Protocols had been modified one after the other so as to save energy during their every transmission. Clustering technique was used and it was found that it is more optimistic way to save energy. In this paper, we propose a new clustering protocol: Threshold Enhanced Developed and Distributed energy-Efficient Clustering Protocol (TEDDEEC) for heterogeneous wireless sensor networks. In this technique, a modified value of threshold is presented on which a node will decide whether to become CH or not. Simulation results show that this protocol outperforms as compared to its conventional counterparts.